2015
DOI: 10.1074/jbc.m115.682401
|View full text |Cite|
|
Sign up to set email alerts
|

High Resolution Structures of the Human ABO(H) Blood Group Enzymes in Complex with Donor Analogs Reveal That the Enzymes Utilize Multiple Donor Conformations to Bind Substrates in a Stepwise Manner

Abstract: Background: Substrate hydrolysis has impeded structural investigation of human ABO(H) glycosyltransferase specificity. Results: Complexes with natural and isosteric non-hydrolyzable donor analogs show multiple stable intermediate donor binding conformations. Conclusion: Subtle stereochemical differences from natural donor prevent isosteric donor analog from displaying full mimicry. Significance: High resolution structural analysis provides insight into inhibitor development and the multistage process of substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…It is interesting to note that ADP in chain B of the CLg1GBSS structure adopts a conformation quite similar to that observed in structures of some GTA-fold glycosyltransferases which have donors with a covalently bound glucosyl group, for example R. marinus MGS (PDB_ID 2bo8 and 2y4m) ( Flint et al, 2005 ; Nielsen et al, 2011 ) and the human blood group glycosyltransferase (PDB_IDs 5c3b and 5c1l) ( Gagnon et al, 2015 ).…”
Section: Discussionsupporting
confidence: 53%
“…It is interesting to note that ADP in chain B of the CLg1GBSS structure adopts a conformation quite similar to that observed in structures of some GTA-fold glycosyltransferases which have donors with a covalently bound glucosyl group, for example R. marinus MGS (PDB_ID 2bo8 and 2y4m) ( Flint et al, 2005 ; Nielsen et al, 2011 ) and the human blood group glycosyltransferase (PDB_IDs 5c3b and 5c1l) ( Gagnon et al, 2015 ).…”
Section: Discussionsupporting
confidence: 53%
“…However, the basis of these allosteric interactions is not understood yet. Interestingly, a recent crystallographic study shows that GTA, GTB, and mutants are able to bind to a variety of conformations of donor substrates, including low‐energy solution conformations . It is suggested that the enzymes shift the donor substrates into the catalytically competent “tucked‐under” conformation in a stepwise fashion.…”
Section: Resultsmentioning
confidence: 99%
“…It has four different phenotypes-A, B, AB, and O-that differ in the carbohydrate antigenst hat are dominantly presented on the cell wall of erythrocytes. [2][3][4][5] Even thought he ABO blood group system has been known for more than 100 years and can be routinelys erotyped, its biological functionr emains elusive. [1] In the Aa nd Bp henotype, the Ha ntigen is modified by the addition of N-acetylgalactosamine (A)o rg alactose (B) that are each transferred by the action of GTAo rG TB, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic basis of their specificity has therefore been studied intensively. [2][3][4][5] Even thought he ABO blood group system has been known for more than 100 years and can be routinelys erotyped, its biological functionr emains elusive. [1] However,alarge body of work has linked blood subgroups, in particularn on-O phenotypes, to the incidence of various cancer types and their progression, although no underlying biological mechanism has been establishedf or this yet.…”
Section: Introductionmentioning
confidence: 99%